Epigenetics Control Microglia Plasticity - Cheray, Mathilde; Joseph, Bertrand (Frontiers in Cellular Neuroscience, 2018)
Microglia, resident immune cells of the central nervous system, fulfil multiple functions in the brain throughout life. These microglial functions range from participation in innate and adaptive immune responses, involvement in the development of the brain and its homeostasis maintenance, to contribution to degenerative, traumatic and proliferative diseases; and take place in the developing, the aging, the healthy, or the diseased brain. Thus, an impressive level of cellular plasticity, appears as a requirement for the pleiotropic biological functions of microglia. Epigenetic changes, including histone modifications or DNA methylation as well as microRNA expression, are important modifiers of gene expression, and have been involved in cell phenotype regulation and reprogramming and are therefore part of the mechanisms regulating cellular plasticity. Here, we review and discuss the epigenetic mechanisms, which are emerging as contributors to this microglial cellular plasticity and thereby can constitute interesting targets to modulate microglia associated brain diseases, including developmental diseases, neurodegenerative diseases as well as cancer.